2022
DOI: 10.3389/fphys.2022.822348
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure Induces Intestinal Barrier Damage and Endoplasmic Reticulum Stress in the Colon via the SIRT1/Nrf2 Signaling Pathway

Abstract: Ambient air temperature is a key factor affecting human health. Long-term exposure to a cold environment can cause various diseases, while the impact on the intestine, the organ which has the largest contact area with the external environment, cannot be ignored. In this study, we investigated the effect of chronic cold exposure on the colon and its preliminary mechanism of action. Mice were exposed to 4°C for 3 hours a day for 10 days. We found that cold exposure damaged the morphology and structure of the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Numerous studies have demonstrated that cold stress can harm a number of mammalian tissues, including the lungs, colon, liver, and hippocampus [7,15,28,33]. In this study, chronic cold stress led to structural damage and in ammatory cell in ltration in the ileum, jejunum and colon of mice.…”
Section: Discussionmentioning
confidence: 59%
“…Numerous studies have demonstrated that cold stress can harm a number of mammalian tissues, including the lungs, colon, liver, and hippocampus [7,15,28,33]. In this study, chronic cold stress led to structural damage and in ammatory cell in ltration in the ileum, jejunum and colon of mice.…”
Section: Discussionmentioning
confidence: 59%
“…[11] Despite an increase in TNF-𝛼 during the high cold stress condition suggesting an increase in intracellular inflammation, no changes were observed in IL-6 in young males (Table 1). This may be attributed to the level of cold stress in the present study representing cold stress-inducing reductions in core temperature that are physiologically relevant to humans, as others have observed elevations in both TNF-𝛼 and IL-6 in the colon of C57BL/6 mice exposed to extreme temperatures of 4 °C for 3 h. [20] Interestingly in the present study, we observed activation of the HSR during moderate cold stress, as represented by elevations in both HSP70 and HSP90 immediately following cold exposure, that were sustained throughout the 3 h recovery (Table 1). Although stressors that upregulate HSPs initially increase autophagy during or immediately following a stress insult (as also shown in the present investigation), HSPs typically upregulate following the cessation of the stressor.…”
Section: The Effect Of In Vivo Cold Exposure On the Autophagic Responsementioning
confidence: 56%
“…[ 11 ] Despite an increase in TNF‐α during the high cold stress condition suggesting an increase in intracellular inflammation, no changes were observed in IL‐6 in young males (Table 1). This may be attributed to the level of cold stress in the present study representing cold stress‐inducing reductions in core temperature that are physiologically relevant to humans, as others have observed elevations in both TNF‐α and IL‐6 in the colon of C57BL/6 mice exposed to extreme temperatures of 4 °C for 3 h. [ 20 ]…”
Section: Discussionmentioning
confidence: 83%
“…Food & Function substances such as Cyt C. 42 It has been shown that prolonged cold stimulation increases the protein levels of Cyt C in the colon and induces apoptosis. 43 Of particular interest, our results showed that PGC1-α was upregulated during prolonged cold stimulation. This implied that the mitochondrial protective mechanisms in the heart of pigs are triggered during prolonged cold stimulation, thereby facilitating the clearance of ROS.…”
Section: Papermentioning
confidence: 63%